Analysis and identification of time-invariant systems, time-varying systems, and multi-delay systems using orthogonal hybrid functions : theory and algorithms with MATLAB® /: theory and algorithms with MATLAB®. (2016) - Deb, Anish, 1951-2021; Roychoudhury, Srimanti; Sarkar, Gautam, 1953-
No abstract available